Epigenetic regulation of integrin β6 transcription induced by TGF‐β1 in human oral squamous cell carcinoma cells. Issue 5 (19th January 2018) - Xu, Mingyan; Yin, Liqin; Cai, Yihuang; Hu, Qingwei; Huang, Jie; Ji, Qing; Hu, Yanping; Huang, Wenxia; Liu, Fan; Shi, Songlin; Deng, Xiaoling
Abstract: Overexpression of integrin αvβ6 is believed to play an important role in the invasion and metastasis of oral squamous cell carcinoma (OSCC). However, little is known about the molecular mechanisms leading to αvβ6 upregulation in OSCC. As the integrin β6 (ITGB6) is the only partner with αv, the expression of αvβ6 is dependent on ITGB6, it is, therefore, pivotal to investigate the mechanisms underlying ITGB6 overexpression in OSCC. We previously reported the cloning and characterization of human ITGB6 gene. In the current study, we further investigated the molecular mechanisms of ITGB6 expression and the upregulation by carcinogenesis related cytokine‐transforming growth factor‐β1 (TGF‐β1) in OSCC cells. We first demonstrated that TGF‐β1 can induce ITGB6 mRNA and protein express in a time and concentration dependent manner, and the induced‐ITGB6 mRNA was not due to increase the mRNA stability, but regulated at transcriptional level. By using a luciferase reporter assay, site‐mutation, RNA interference, and chromatin immunoprecipitation assay, we revealed for the first time that JunB, a member of the activator protein‐1 (AP‐1) family, is involved in the positive regulation to the ITGB6 transcription induced by TGF‐β1 in OSCC cells. Furthermore, our data also demonstrated that histone acetyltransferase (HAT) CBP mediated histone H3 and H4 hyperacetylation, and RNA Polymerase II recruitment to ITGB6 promoter, facilitated the binding of transcription factor JunB to ITGB6 promoter after TGF‐β1 stimulation. Collectively, these findings demonstrate that JunB and CBP‐mediated histone hyperacetylation are responsible for TGF‐β1 induced ITGB6 transcription in OSCC cells, suggesting that epigenetic mechanisms are responsible for the active transcription expression of ITGB6 induced by TGF‐β1 in OSCC cells. Abstract : Overexpression of integrin β6, only partnering with αv, is believed to play an important role in the invasion and metastasis of oral squamous cell carcinoma (OSCC). Carcinogenesis related cytokine‐transforming growth factor‐β1 (TGF‐β1) induced integrin β6 is through histone acetyltransferases (HAT) CBP mediated histone H3 and H4 acetylation, and cooperation with transcription factor JunB activation at integrin β6 promoter.